2021
DOI: 10.1093/narcan/zcab033
|View full text |Cite
|
Sign up to set email alerts
|

Androgen signaling connects short isoform production to breakpoint formation at Ewing sarcoma breakpoint region 1

Abstract: Ewing sarcoma breakpoint region 1 (EWSR1) encodes a multifunctional protein that can cooperate with the transcription factor ERG to promote prostate cancer. The EWSR1 gene is also commonly involved in oncogenic gene rearrangements in Ewing sarcoma. Despite the cancer relevance of EWSR1, its regulation is poorly understood. Here we find that in prostate cancer, androgen signaling upregulates a 5′ EWSR1 isoform by promoting usage of an intronic polyadenylation site. This isoform encodes a cytoplasmic protein tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 65 publications
(79 reference statements)
0
2
0
Order By: Relevance
“…A similar process could occur in the DSRCT cell of origin to initiate EWSR1::WT1 translocation. This hypothesis is bolstered by recent findings from Nicholas et al showing that AR binds to introns 5 and 8 of EWSR1 in prostate cancer and further, that R1881 treatment can increase chromosomal breakage at this site in an R-loop dependent manner 31 . In fact, intron 7 of EWSR1, located between the two AR binding sites, is the most common breakpoint location in DSRCT.…”
Section: Discussionmentioning
confidence: 95%
“…A similar process could occur in the DSRCT cell of origin to initiate EWSR1::WT1 translocation. This hypothesis is bolstered by recent findings from Nicholas et al showing that AR binds to introns 5 and 8 of EWSR1 in prostate cancer and further, that R1881 treatment can increase chromosomal breakage at this site in an R-loop dependent manner 31 . In fact, intron 7 of EWSR1, located between the two AR binding sites, is the most common breakpoint location in DSRCT.…”
Section: Discussionmentioning
confidence: 95%
“…It has been reported that highly active transcription of the EWSR1 locus could induce the formation of R-loops that in turn favor double-strand breaks. Nicholas et al [29], using prostate cancer cell lines, reported that androgen receptors promoted breakpoint generation in an intronic polyadenylation site of EWSR1 near the Ewing sarcoma breakpoint hotspot, which was dependent on the formation of R-loops. Indeed, persistent R-loops are a direct cause of chromosomal rearrangements [30].…”
Section: Discussionmentioning
confidence: 99%